Pre-registration and Its Alternatives to Foster Open Science in Universities - Cem Birol (027.7)
Research pre-registration entails the open declaration of a project’s research design before publication. It aims to prevent scholars from promoting their research based on shady, non-reproducible statistical findings. While most scholarly debate focuses on whether pre-registration improves the quality of individual research, this paper discusses whether universities should enforce a pre-registration mandate to solve the research replicability problem at a higher level. It highlights that pre-registration can improve the quality of scientific research. However, there are two more effective means to combat nonreplicable research problems at university administrative and library levels. First, universities can enhance their enforcement mechanisms for Data Management Plans that scholars often must prepare to secure funding. Second, university libraries and administrative offices can cooperate to inform graduate students and junior scholars about refereed journals that publish null findings. Both measures outperform pre-registration because they are bureaucratically more justifiable to implement for universities than the latter.